The greater East Asia co-prosperity sphere : when total empire met total war - Yellen, Jeremy A., 1977- (Ithaca : Cornell University Press, 2019)
"This book explores the Greater East Asia Co-Prosperity Sphere, Japan's ambitious wartime attempt to create a new order in East and Southeast Asia"--
Introduction : when total empire met total war -- Into the tiger's den -- Order begets war -- Imagining co-prosperity -- The patriotic collaborators -- A new deal for greater East Asia? -- Independence in transition.
First published 2019
Includes bibliographical references and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Greater East Asia Co-prosperity Sphere -- History; Japan -- Relations -- East Asia; East Asia -- Relations -- Japan; Japan -- Relations -- Philippines; Philippines -- Relations -- Japan; Japan -- Relations -- Burma; Burma -- Relations -- Japan; Japan -- History -- 20th century